Can micro coffee enterprises create opportunities for women? Evidence from coffee micro-mills from Costa Rica's Los Santos region, Tarrazu coffee - Nunes-Solis, Milagro (Instituto de Desarrollo Rural, Costa Rica, 2019)
Presented by Milagro Nunes-Solis (INDER), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.